2019
DOI: 10.3389/fonc.2019.00725
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes Comparison of Endoscopic Resection With Gastrectomy for Treatment of Early Gastric Cancer: A Systematic Review and Meta-Analysis

Abstract: Background: Endoscopic resection (ER) and gastrectomy have been both accepted as curative treatments for early gastric cancer. We intended to compare ER with gastrectomy treatments on safety of patients, disease-free survival and overall survival for early gastric cancer through this systematic review. Methods: A literature search was performed in Pubmed, Embase, and Cochrane Library databases. Studies that have compared ER with gastrectomy for early gastric cancer were inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 39 publications
2
10
0
Order By: Relevance
“…This may be because the prospective study included patients with good performance status (ECOG 0 and 1) and excluded those with severe underlying illness. Our results are also consistent with recent systematic reviews that compared ESD or endoscopic resection with surgery for EGC meeting the expanded criteria [17][18][19][20]. Therefore, our study suggests that the OS after curative ESD may be comparable to that after surgery for UD EGC.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This may be because the prospective study included patients with good performance status (ECOG 0 and 1) and excluded those with severe underlying illness. Our results are also consistent with recent systematic reviews that compared ESD or endoscopic resection with surgery for EGC meeting the expanded criteria [17][18][19][20]. Therefore, our study suggests that the OS after curative ESD may be comparable to that after surgery for UD EGC.…”
Section: Discussionsupporting
confidence: 92%
“…In recent years, several systematic reviews reported that overall survival (OS) was comparable between ESD and surgery for patients with EGC meeting the expanded criteria [16][17][18][19][20]. However, these studies included both differentiated-type and UD EGC and did not evaluate the outcomes for UD EGC separately.…”
mentioning
confidence: 99%
“…[ 1 , 2 ] Compared with radical gastrectomy, ESD can preserve intact organs and provide a better life quality after ESD. [ 3 , 4 ] However, the incidence of metachronous gastric neoplasms (MGN) after ESD is higher than that after radical gastrectomy. According to previous studies, the MGN rate after ESD was 2.7% to 15.6%, [ 5 , 6 ] while the rate after surgery ranged from 0.1% to 3.0%.…”
Section: Introductionmentioning
confidence: 99%
“…Resections are performed through various endoscopic techniques,which are used in early stage gastric cancer cases or precancerous gastric lesions, with the gradual spread of minimally invasive methods today and researchers have underlined in comparisons with surgerythat similar oncological results were obtained with lower morbidity rates. [2,3] Accurate pathology assessment is a critical component of predicting the long-term results of endoscopic resection in the treatment of these lesions. Numerous studies have been conducted over the years on the pathology assessment of resected specimen and various techniques have been employed in guidelines as to the ways in which the samples could be fixed and transferred to pathology laboratories.…”
Section: Discussionmentioning
confidence: 99%
“…E ndoscopic Mucosal Resection (EMR), a part of minimally invasive surgery,was first described in 1974 and has become a commonly performed procedure due to its acceptable oncological results in the treatment of precancerous lesions and early stage gastric cancers along with its low cost and morbidity rates as has been reported by many studies in literature. [1][2][3] Further, endoscopic submucosal dissection (ESD) technique has been described thanks to the increase in EMR experience and the related developing endoscopy techniques and equipment [4] and it facilitated the resection of larger lesions. Moreover, endoscopic full thickness resection (EFTR) technique has also been described for the resection of fibrotic or subepithelial lesions in cases where the EMR/ESD technique was not fitting.…”
mentioning
confidence: 99%